A bibliometric analysis of communication skills among social sciences students in higher education - Taqwa, Muhammad Reyza Arief; Panya, Napat (Priviet Social Sciences Journal, 2026)
Communication skills among social-science students in higher education (CS3HE) is a rapidly growing research area. This study aims to analyze research trends on this topic through a bibliometric analysis of 1,554 documents published in Scopus-indexed journal articles. The results highlighted an increasing number of publications since 2015. The research was conducted by researchers from multiple countries. The results of research on the CS3HE topic have also been widely published in reputable journals, with most of them being published in Q1 journals. The collaboration between authors and countries shows that this research topic has received significant attention globally. Based on the analysis of research trends, future research should continue to explore the application of technology in health education and the development of communication skills to improve interactions between medical personnel and patients.